(untitled) (Comprehensive Journal of Science, 2025)
The study aimed to investigate the most important challenges facing the banking system in Libya, to implementing the three pillars of the Basel (II), through a representative sample of the population, which is the risk management employees in commercial banks in eastern Libya, in addition to the risk management employees in the Central Bank of Libya branch (Benghazi), as they are concerned with the Basel Accord and its requirements. The researcher used the questionnaire to collect the study data and test its hypotheses, through a One Sample T Test, to test the first main hypothesis, which states that there are no challenges towards adopting a regulatory framework for the pillars of the Basel (II) convention, and independent T test, to test the differences in the respondents’ answers towards the challenges of implementing the requirements of Basel (II) attributed to bank ownership. The results of the study indicate that there are no statistically significant challenges facing the Libyan banking system regarding the first and second pillars related to quantitative capital requirements and supervisory review, and that there are statistically significant challenges towards implementing the third pillar related to financial market discipline. The study showed statistically significant differences in participants’ responses to these challenges in favour of the public sector. The study recommends the importance of ensuring the availability of success factors to implement the three Basel pillars, such as competent employees, advanced infrastructure, and information systems characterized by efficiency, accuracy, and objectivity. It also recommends strengthening the role of the regulatory authority in encouraging commercial banks to adopt internal methods for measuring risks, and facilitating the establishment of institutions to assess creditworthiness Locally.